Performance evaluation of air flow and thermal comfort in the room with Wind-Catcher using different CFD techniques under neutral Atmospheric Boundary Layer - Ahmed Kabir, I.F.S. (Elsevier Ltd, 2017)
Energy usage in buildings using conventional Heat Ventilation Air Conditioning (HVAC) systems can be considerably reduced on using natural ventilation systems like wind catcher. In addition to high energy consumptions in conventional HVAC, other disadvantages include ozone layer depletion due to CFCs emitted and also cost involved in installation and maintenance. Purpose of this study was to investigate the airflow and thermal comfort analyses of existing common wind catcher design in the city of Yazd using computational fluid dynamics (CFD) technique. In order to have more realistic analysis, neutral homogenous atmospheric boundary layer (ABL) was created at the inlet. Standard k-e turbulence model was used since equations for creating ABL were more related to this model. 3D CFD analysis was performed using both ANSYS FLUENT and OPENFOAM. Thermal comfort analysis was evaluated based on ASHRAE standard 55. © 2017 The Authors. Published by Elsevier Ltd.